2021
DOI: 10.3389/fcell.2021.700827
|View full text |Cite
|
Sign up to set email alerts
|

Massive Gene Loss and Function Shuffling in Appendicularians Stretch the Boundaries of Chordate Wnt Family Evolution

Abstract: Gene loss is a pervasive source of genetic variation that influences species evolvability, biodiversity and the innovation of evolutionary adaptations. To better understand the evolutionary patterns and impact of gene loss, here we investigate as a case study the evolution of the wingless (Wnt) family in the appendicularian tunicate Oikopleura dioica, an emergent EvoDevo model characterized by its proneness to lose genes among chordates. Genome survey and phylogenetic analyses reveal that only four of the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 79 publications
4
15
0
Order By: Relevance
“…In summary, this provides a complex network of mutational protection, and thus the loss of one of these redundant/complementary Wnt factors (caused by either depletion of the gene, or regulatory changes) may not alter the development of the organism very much. Indeed, it has been shown that function-shuffling occurs regularly in Wnt genes, often associated with gene loss [ 52 , 56 , 84 ]. The latter, however, is not mandatory, especially when the gene is part of multiple GRNs.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this provides a complex network of mutational protection, and thus the loss of one of these redundant/complementary Wnt factors (caused by either depletion of the gene, or regulatory changes) may not alter the development of the organism very much. Indeed, it has been shown that function-shuffling occurs regularly in Wnt genes, often associated with gene loss [ 52 , 56 , 84 ]. The latter, however, is not mandatory, especially when the gene is part of multiple GRNs.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that spatio-temporal intersection is not unique to the more complex gene family in the mouse. Evolutionary studies comparing Amphioxus and the tunicate Oikopleura dioica have suggested three modes of evolutionary change in the Wnt gene family namely, conservation of function, function shuffling and gene loss (Martí-Solans et al, 2021). It is possible that the co-expression of subdomains of different Wnts in the mouse reflects the operation of a conserved ancestral regulation, though not necessarily conservation of precise gene function, across different Wnts.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative hypothesis is the loss of extensive genomic regions or chromosomes on which L-and M-type ITS1s are clustered. Adaptive phenotypic diversity due to gene loss (Olson 1999;Albalat and Cañestro 2016;Marti-Solans et al 2021) may have been associated with the morphological transformation of hermit crabs to king crabs. ochotensis, GT: Elassochirus cavimanus).…”
Section: Evolutionary Relationships Between Its1 Types and Between Taxamentioning
confidence: 99%